Different reaction mechanisms of SO4•− and •OH with organic compound interpreted at molecular orbital level in Co(II)/peroxymonosulfate catalytic activation system - Zhang, Huixuan; Xie, Chenghan; Chen, Long; Duan, Jun; Li, Fan; Liu, Wen (Water research (Oxford), 2023)
•Dynamic electronic structure analysis is applied to reveal radical attack mechanism.•SO4•− has higher oxidation potential and electrophilic index than •OH.•Only SO4•−can react with CAF through single electron transfer reaction (SET) route.•Only •OH can react with CAF through hydrogen atom abstraction (HAA) route.••OH shows larger energy barriers than SO4•− through radical adduct formation (RAF). Hydroxyl radical (•OH) and sulfate radical (SO4•−) produced in advanced oxidation processes (AOPs) have been widely studied for organic contaminants degradation, however, the different radical characteristics and reaction mechanisms on organics degradation are still needed. In this study, a homogeneous Co(II)/peroxymonosulfate activation system was established for caffeine (CAF) degradation, and pH was controlled to regulate the radicals production. The different attack routes driven by SO4•− and •OH were deeply explored by transformation products (TPs) identification and theoretical calculations. Specifically, a method on dynamic electronic structure analysis of reactants (R), transition state (TS) and intermediates (IMs) during reaction was proposed, which was applied to elucidate the underlying mechanism of CAF oxidation by •OH and SO4•− at the molecular orbital level. In total, SO4•− is kinetically more likely to attack CAF than •OH due to its higher oxidation potential and electrophilicity index. Single electron transfer reaction (SET) is only favorable for SO4•−due to its higher electron affinity than •OH, while only •OH can react with CAF via hydrogen atom abstraction (HAA) route. Radical adduct formation (RAF) is the most favorable route for both •OH and SO4•− attack according to both kinetics and thermodynamics results. These findings can significantly promote the understanding on the degradation mechanism of organic pollutants driven by •OH and SO4•− in AOPs. [Display omitted]